Public entrepreneurship, municipal performance, and political capacity's moderating role in Niger state - Ahmed, Mohammed; Umar, Mohammed-Bello Habiba (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – This study investigates the moderating role of political capacity (PC) in the relationship between public entrepreneurship (PE) and local government performance (LGP) in Niger State, Nigeria, using structural equation Modelling (SEM).Methodology – This study is a quantitative research based on a sample of 1,396 employees from four local government areas in Niger State, Nigeria. A non-probability sampling method was utilized, and the data were analyzed using STATA version 17 to obtain descriptive statistics, perform a normality test, assess factor loadings, and conduct correlation and SEM analyses.Findings – The analysis revealed that the mean values of public entrepreneurship, political capacity, and local government performance were low. The SEM analysis found that political capacity significantly moderates the relationship between public entrepreneurship and local government performance and establishes a direct relationship between public entrepreneurship, political capacity, and the performance of local governments.Implications – This study suggests that political capacity should be considered in the administration of local governments, as it can lead to more effective management of municipalities.Originality – No previous research has explored the relationship between political capacity, public entrepreneurship, and local government performance using SEM in the context of local government administration.